Manusia yang Mewahyu Menurut Al-Faraby - Achmad Bahrur Rozi (Jurnal Filsafat "WISDOM", 2004)
In Islam, apocalipse own to domicile central as communications media between God with the human being. Apocalipse meant as a guide by Muhammadan majority. Process of the apocalipse be deemed to have ended. Al Faraby, a Muslim philosopher, is differed from the public oponion. Apocalipse accroding to Al Faraby is an ability of mind where human being reacheh the ecquirement level (mind mustafad). This mind basically is infinite potency from ruh blown by God in early creation.Human being is spiritual being while apocalipse is ability of psychological human being for the transcendece. At the certain level infinite potency from this Psyche earns the communication with the tenth Mind created by God through emanation. God think of His self. Opinion represent the energy. God Opinion energy is Omnipoten. What big the most and super to the most created the First Mind. That way further till tenth Mind. Tired human being Mind of tenth Mind basically have apocalipse (able to communicate Occult)